Measurement methods and mathematical model of main characteristics of waveguide-coaxial connectors - Eduard Glushechenko (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Modern complex microwave radio electronic systems may use functional devices implemented on different types of transmission lines. In order to connect such devices to each other to form antenna feed system, the following three types of special connectors can be used: coaxial, waveguide, and combined microwave devices based on waveguide and coaxial segments. The main electrical characteristics of waveguide coaxial connectors (WCC) are the losses introduced by the device to the antenna feed and matching with the regular microwave path (voltage standing-wave ratio, VSWR). Standard methods and standard equipment used to measure the characteristics of coaxial or waveguide connectors cannot be applied to WCCs. This article proposes a method designed to measure the main characteristics of waveguide-coaxial connectors and presents their mathematical model (wave matrices). The proposed methods of measuring microwave characteristic are demonstrated on the example of waveguide coaxial connectors of longitudinal coaxial type. It should be noted that the proposed technique has been experimentally tested on a number of specific devices. Not only the waveguide coaxial connectors have been studied in different frequency ranges (waveguide sizes from 23×5 to 58×25 mm), but also with different coaxial channel designs (sizes 3.5/1.52; 6.0/2.6 and 7.0/3.04 mm). The proposed method provides replicable measurements results of the characteristics of waveguide coaxial connectors, which confirms its reliability.